Entre o olhar da pobreza e o som da ostentação : o consumo das narrativas midiáticas do funk ostentação por crianças em contextos de vulnerabilidade social - Rezende, Aline da Silva Borges (2017)
In the cultural circuit of funk ostentation, the periphery overflows and fades territorial delimitations, making it possible to transpose, through the imaginary paths of songs and audiovisual aesthetics of this musical genre, the reality of poverty experienced by children and young people peripheral to the symbolic universe for the consumption of Lux. It is with this contextual panorama that this research aims to investigate the uses and modes of appropriation of the mediatic narratives of the funk ostentation by a group of children, from 6 to 12 years of age, living in the largest favela on stilts in Brazil, community of the Vila Gilda Dam, in Santos, a coastal municipality of São Paulo. Based on the theoretical reflections on peripheries, childhood and social vulnerability, articulated to the studies on entertainment narratives and media consumption, in consonance with the concepts of bastardy, music listening, sound landscapes, performativity and mimesis in culture, this research endeavors to explore specific contexts of reception of funk ostentation, as well as the cultural and social circuits that engender this musical genre. Thus, the study problematizes whether the expressions that refer to the imagery of consumption, celebrity and social projection, embodied in the productions of funk ostentation, corroborate the maintenance of a capitalist and exclusive status quo or, in some way, refract the reality of poverty and precariousness experienced by these children.